2021
DOI: 10.1186/s12959-021-00274-x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of treatment of cancer-associated venous thromboembolism

Abstract: Patients with cancer are prone to develop venous thromboembolism (VTE) that is the second leading cause of mortality among them. Cancer patients with VTE may encounter higher rates of VTE recurrence and bleeding complications than patients without cancer. Treatment of established VTE is often complex in patients with cancer. Treatment of cancer-associated VTE basically comprises initial treatment, long-term treatment, treatment within 6 months, treatment beyond 6 months, treatment of recurrent VTE, and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…LMWH was received by a substantial number of patients at discharge (35.0%), the majority of whom presented with a co-existing malignancy. The choice of anticoagulation for cancer-associated VTE is a major therapeutic challenge due to a delicate balance between the recurrent thromboembolic and bleeding events in these patients [20]. LMWH has traditionally been the standard treatment for cancer-associated VTE due to higher efficacy and comparable safety, compared to VKA [21].…”
Section: Discussionmentioning
confidence: 99%
“…LMWH was received by a substantial number of patients at discharge (35.0%), the majority of whom presented with a co-existing malignancy. The choice of anticoagulation for cancer-associated VTE is a major therapeutic challenge due to a delicate balance between the recurrent thromboembolic and bleeding events in these patients [20]. LMWH has traditionally been the standard treatment for cancer-associated VTE due to higher efficacy and comparable safety, compared to VKA [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is of note that all three treatment options were equal regarding all-cause mortality [ 38 ]. Patients’ preference over an oral anticoagulant than an injectable LMWH may affect the final clinical decision [ 40 ].…”
Section: Considerations On the Current Literaturementioning
confidence: 99%
“…Armand Trousseau first observed the association between malignant disease and thromboembolism in the nineteenth century by realizing the major medical impact this haemostatic disorder had on cancer patients’ prognosis [ 30 ]. In fact, the blood hypercoagulation state in the context of cancer followed by the diagnosis of VTE, known as the Trousseau syndrome, is nowadays remarkably well-recognized and, aside from the malignant neoplasia itself, is the second most frequent cause of death among these patients [ 31 , 32 ]. Several studies have demonstrated a growing incidence of cancer-related thrombosis, which can be explained by patient- (e.g., advanced age), cancer biology- (e.g., primary tumour site, histology, size and stage) and cancer treatment-related factors (e.g., surgery, chemotherapy and radiotherapy) [ 28 , 30 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%